Single Incision Laparoscopic Ventral Hernia Repair - Bower, Curtis E.; Love, Katie M. (My University, 2011)
Background and Objectives: Laparoscopic ventral hernia repair (LVH) requires several skin incisions for trocar placement. We have developed a single incision approach to LVH repair. The technique was introduced in clinical practice to any consenting patients who were candidates for a standard multi-port laparoscopic hernia repair. A consecutive series of patients was then followed to evaluate feasibility. Methods: Over an 8-month period, 14 patients (9 females, 5 males) underwent LVH repair by an academic surgeon. One of 2 access methods was used in each patient through a single 1.5-cm to 2-cm skin incision. One technique utilized two 5-mm ports with a temporarily placed 11-mm port for mesh insertion. The second technique utilized the SILS port (Covidien, Norwalk, CT). Standard or roticulating laparoscopic instruments were used with both techniques. Results: Range (mean) BMI: 23 to 59 (38), Age: 26 to 73 years (53), Duration: 37 to 87 minutes (57), Defect size: 1cm to 8cm (2), 3 with Swiss-cheese defect hernias. The procedure was successfully performed in all patients. No conversions to a multiple-port approach or to an open procedure were necessary. There were no mortalities, major complications, or recurrences during the mean follow-up period of 4 weeks. Conclusion: Single incision ventral hernia repair is technically feasible, effective, and reproducible. The technique is easy to master, and safe for any patient who is a candidate for laparoscopic ventral hernia repair. Further data collection with long-term follow-up will be needed to ensure equivalent outcomes. There will be demand for this approach by patients for cosmetic reasons, and it may serve as a bridge to natural orifice techniques.
Keywords: Ventral hernia; Laparoscopy